Ion-implanted deuterium release behavior from Li-based advanced ceramics - Tolstolutskaya, G.D.; Karpov, S.A.; Ruzhytskiy, V.V.; Nikitin, A.V. (Problems of Atomic Science and Technology, 2022)
The behavior of ion-implanted deuterium in advanced lithium orthosilicate (Li₄SiO₄) pellets with addition of lithium metatitanate (Li₂TiO₃), and in reference Li₄SiO₄ pellets, has been studied. Thermal desorption spectroscopy (TDS) was used to examine the deuterium interaction with radiation defects in materials. Deuterium gas release from studied ceramics has revealed a clear dependence of deuterium trapping behavior on phase composition. The trap strength of radiation defects formed in lithium titanate was found to be higher than in lithium orthosilicate.